Reversed Discrepancy between CT and Diffusion-Weighted MR Imaging in Acute Ischemic Stroke - Kim, E.Y. (AJNR Am J Neuroradiol, 2006)
PURPOSE: We sought to determine whether an early CT ischemic lesion showing parenchymal hypoattenuation might be undetectable on diffusion-weighted imaging (DWI) in acute cerebral ischemia. MATERIALS AND METHODS: We retrospectively evaluated CT and MR images of 70 consecutive patients with acute middle cerebral artery (MCA) infarction. All patients underwent CT and MR imaging within 6 hours of symptom onset. We determined the presence of reversed discrepancy (RD), defined as an early ischemic lesion showing parenchymal hypoattenuation on CT but no hyperintensity on DWI. CT Hounsfield units (HU), apparent diffusion coefficients (ADCs), and perfusion parameters were calculated for RD lesions. RESULTS: RD was found in 9 (12.9%) patients and at basal ganglia (89%). The mean HU of RD lesion was lower than that of normal tissue (ΔHU, 2.33 ± 0.74, P < .001). RD lesions showed no significant decrease of ADC (ADC ratio, 0.97 ± 0.07, P = .059) and cerebral blood flow (relative CBF, 0.87 ± 0.20, P > 0.05). Delayed DWI hyperintensity occurred in 8 (88.8%) RD lesions, and all lesions progressed to infarction. In 6 (66%) of 9 patients with RD, Alberto Stroke Program Early CT scores of ischemic lesions were lower on CT than those on DWI. CONCLUSION: RD was uncommonly found mainly in basal ganglia, and all RD lesions progressed to infarction at follow-up. Early CT ischemic lesion showing parenchymal hypoattenuation may be undetectable on DWI, and DWI may underestimate extent of severe ischemic tissue in patients with acute MCA infarction.